Desenvolvimento de plataforma biofotônica para detecção plasmática da sepse: Estudo pré-clínico de prova de conceito - Vilarinho, Glauciane Silva (2023)
Sepsis is a systemic response with different clinical stages against an infectious agent such as bacteria, viruses, fungi, or protozoa. Currently, early diagnosis presents a clinical challenge to reduce its high mortality rate, in addition to generating a high cost of treatment in public and private health sectors. In this context, the present study search to identify potential plasmatic biomarkers based on a biophotonic technology by ATR-FTIR aiming at screening or diagnosing sepsis in a preclinical study. For this, a murine model of sepsis was established by cecal ligation and puncture (CLP). Sixteen rats were randomly divided into control (n=8) and sepsis (n=8) groups. The animals were euthanized 24h after sepsis induction and blood was collected. Blood plasma was analyzed using an ATR-FTIR platform and univariate and multivariate analyzes were used to screen for potential spectral biomarkers of sepsis in plasma. The presence of sepsis was confirmed by an increase (p < 0.05) in C-reactive protein concentration compared to controls. In the absorbance normalized spectrum, the band area between 2945-2888 cm-1 was reduced (p<0.05) in animals with sepsis compared to controls. The analysis of the band area in the region 2945-2888 cm-1 indicated a sensitivity of 87.5% and a specificity of 75%. In the second derivative spectrum, the vibrational mode at 1513 cm-1 was also reduced (p<0.05) in animals with sepsis compared to controls. Analysis of the height of the valley at 1513 cm-1 indicated a sensitivity of 75% and specificity of 87.5%. In conclusion, these results indicate that ATR-FTIR spectroscopy supported with univariate analysis has the potential to provide an alternative for the detection of sepsis without the use of reagents, sustainably, and rapidly using blood plasma samples.